Neuromuscular Blockade Correlates with Hormones and Body Composition in Acromegaly. (14th December 2020) - Zhang, Yu; Guo, Xiaopeng; Tan, Gang; Zhao, Mengyun; Huang, Yuguang; Chen, Wei; Shi, Xiaodong; Pei, Lijian; Xing, Bing
Abstract : Tumor resection is the first-line therapy for acromegaly patients. In some cases, unsatisfactory intraoperative neuromuscular blockades (NMBs) lead to failed operations. The purpose of this study was to investigate and quantify the NMB status of acromegaly patients and explore the relationship between NMB status and hormone levels and body composition. Twenty patients with untreated acromegaly and seventeen patients with nonfunctioning pituitary adenomas as controls were enrolled in this study. NMB was assessed using the train-of-four (TOF) technique with TOF-Watch® SX. The onset time of NMB, deep neuromuscular blockade duration (DNMBD), and clinical neuromuscular blockade duration (CNMBD) were monitored. We found a significantly longer onset time (110.25 ± 54.90 vs. 75.00 ± 27.56, s, p = 0.017 ), shorter DNMBD (21.99 ± 5.67 vs. 34.96 ± 11.04, min, p < 0.001 ), and shorter CNMBD (33.26 ± 8.09 vs. 46.21 ± 10.89, min, p < 0.001 ) in acromegaly patients compared with the controls. DNMBD and CNMBD decreased in patients with decreasing body fat percentage and increasing growth hormone (GH) level, insulin-like growth factor 1 (IGF-1) level, and GH and IGF-1 burden. The onset time increased with increasing IGF-1 level and GH and IGF-1 burden. Taken together, a unique NMB status was identified in acromegaly patients with the following characteristics: prolonged onset time and shortened DNMBD and CNMBD. Changes in the levels and burdens of GH and IGF-1 and body composition were linearly correlated with intraoperative NMB in acromegaly patients.